Spatial changes in leaf biochemical profile of two tea cultivars following cold storage under two different vapour pressure deficit (VPD) conditions. (30th March 2019) - Collings, Emma R.; Carmen Alamar, M.; Redfern, Sally; Cools, Katherine; Terry, Leon A.
Highlights: Cold withering emphasised temporal changes in caffeine and theobromine content. Spatial variations in catechin content observed between bud, large leaf and stem. Vapour pressure deficit (VPD) conditions differentially affected caffeine levels. Implications of mechanically harvested tea on final quality are discussed. Abstract: Withering is considered a crucial stage of black tea processing. In this study, tea shoots from two cultivars (cvs. Yabukita and Clone 2) were stored at 5 °C, in either a low or high vapour pressure deficit (VPD) environment, to determine the impact of different withering rates on physiology ( viz . respiration rate [RR], colour and moisture loss) and biochemical profile ( viz . individual catechins, methylxanthines) of tea shoots ( Camellia sinensis ). Low VPD and high VPD conditions during withering increased caffeine levels in Clone 2 and Yabukita, respectively ( p  < 0.05). Caffeine levels steadily increased over time in both cultivars ( p  < 0.05), coinciding with a rapid decline in theobromine (TB). Furthermore, stems contained lower epigallocatechin gallate (EGCG) and caffeine ( ca . 75 and 56%, respectively) compared to bud and larger leaf (LL) ( p  < 0.05). Overall, the results of this study highlight factors such as mechanical harvesting, and hard or soft withering, which could affect final tea beverage quality.